Modified lithium-rich manganese-based material and preparation method and application thereof

By introducing spinel phase and oxygen vacancies on the surface of lithium-rich manganese-based materials to form a specific layered structure, the problem of insufficient material rate performance and cycle stability is solved, and the excellent performance of the material under high magnification and multiple cycles is achieved.

CN114335509BActive Publication Date: 2025-03-21SOUTH CHINA NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210003895.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-04
Publication Date
2025-03-21
Estimated Expiration
2042-01-04

AI Technical Summary

Technical Problem

现有富锂锰基材料在倍率性能和循环稳定性方面存在不足,尤其是氧阴离子的不可逆损失和电荷转移速率较慢的问题,导致材料的倍率性能和循环稳定性较差。

Method used

By introducing spinel phase and specific proportions of oxygen vacancies on the surface of lithium-rich manganese-based materials, a spinel phase layer and a layered phase layer are formed, and a three-dimensional lithium ion channel is provided using spinel phase to improve the diffusion rate of lithium ions, and the precipitation of irreversible oxygen is suppressed through oxygen vacancies to reduce structural rearrangement.

Benefits of technology

The modified material has significantly improved rate performance and cycle stability, and can maintain a high discharge specific capacity at high rates and maintain a high capacity retention rate after multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114335509B_ABST
    Figure CN114335509B_ABST
Patent Text Reader

Abstract

The present invention relates to a modified lithium-rich manganese-based material, a preparation method thereof, and an application. The modified lithium-rich manganese-based material includes a spinel phase layer of a lithium-rich manganese-based material containing a first oxygen vacancy and a layered phase layer of a lithium-rich manganese-based material containing a second oxygen vacancy. Among them, the spinel phase layer coats the layered phase layer. The chemical formula of the lithium-rich manganese-based material is #imgabs0# 0 < x < 1. The spinel phase of the lithium-rich manganese-based material accounts for 1% to 10% of the mass percentage of the modified lithium-rich manganese-based material, and the first oxygen vacancy accounts for 1 at% to 5 at% of the oxygen atoms of the modified lithium-rich manganese-based material. The cooperation of the spinel phase and the oxygen vacancy in the above outer surface coating layer makes full use of the spinel coating layer to provide a three-dimensional lithium ion channel to accelerate the diffusion of Li + and reduce the erosion of the electrolyte on the main structure of the material, which can inhibit the precipitation of irreversible oxygen, so that the modified material has better rate performance and cycle stability when used as an electrode in a lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium battery materials, and particularly to a modified lithium-rich manganese-based material, a preparation method thereof, and an application thereof. Background Art

[0002] The layered lithium-rich oxide cathode xLi2MnO3·(1-x)LiMO2 (M = transition metals such as Mn, Ni, and Co) has advantages such as high discharge specific capacity, low cost, and environmental friendliness, and is very likely to become the next-generation commercial cathode material for lithium-ion batteries. Its high specific capacity comes not only from the redox reaction of transition metal (TM) cations, but also oxygen anions participate in the redox reaction (O 2- →O n- ), contributing additional capacity. However, the participation of lattice oxygen in the reaction is extremely likely to cause irreversible loss of oxygen, and the charge transfer rate is slow during this reaction process; at the same time, the irreversible precipitation of oxygen exacerbates the migration of transition metals to nearby lithium vacancies, forming an amorphous rock salt phase, which hinders the deintercalation and intercalation of lithium ions, resulting in poor rate performance and cycle stability performance. Summary of the Invention

[0003] Based on this, the main object of the present invention is to provide a modified lithium-rich manganese-based material, a preparation method thereof, and an application thereof, which can improve the rate performance and cycle stability of the battery.

[0004] The present invention provides a modified lithium-rich manganese-based material, including a spinel phase layer of a lithium-rich manganese-based material containing a first oxygen vacancy and a layered phase layer of a lithium-rich manganese-based material containing a second oxygen vacancy, wherein the spinel phase layer coats the layered phase layer, and the chemical formula of the lithium-rich manganese-based material is 0 < x < 1, the spinel phase of the lithium-rich manganese-based material accounts for 1% - 10% of the mass percentage in the modified lithium-rich manganese-based material, the first oxygen vacancy accounts for 1 at% - 5 at% of the oxygen atoms of the modified lithium-rich manganese-based material, and the second oxygen vacancy accounts for 1 at% - 3 at% of the oxygen atoms of the modified lithium-rich manganese-based material.

[0005] In one embodiment, the spinel phase of the lithium-rich manganese-based material accounts for 3% - 9% of the mass percentage in the modified lithium-rich manganese-based material, and the first oxygen vacancy accounts for 1 at% - 4 at% of the oxygen atoms of the modified lithium-rich manganese-based material.

[0006] In one embodiment, the thickness of the spinel phase layer of the lithium-rich manganese-based material is 5 nm - 15 nm.

[0007] The present invention further provides a preparation method of a modified lithium-rich manganese-based material, including the following steps:

[0008] S10: preparing a first metal salt according to the ratio of metal nickel, metal cobalt and metal manganese in the above-mentioned lithium-rich manganese-based material, mixing the first metal salt with a precipitant in a mass ratio of (1-3):(2-5), performing a first heat treatment, and preparing a precursor;

[0009] S20: mixing the precursor and the lithium salt at a molar ratio of the first metal in the precursor to lithium of 1:(1-2), performing a second heat treatment, and preparing a pre-modified lithium-rich manganese-based material;

[0010] S30: dispersing the pre-modified lithium-rich manganese-based material in an acid aqueous solution with a pH value of 5 to 7, filtering and then performing a third heat treatment.

[0011] In one embodiment, in step S10, the anion in the metal salt is selected from at least one of acetate, sulfate and nitrate.

[0012] In one embodiment, in step S10, the temperature of the first heat treatment is 150° C. to 600° C., and the time of the first heat treatment is 10 h to 25 h.

[0013] In one embodiment, in step S10, the precipitant is selected from at least one of ammonium bicarbonate, urea and sodium carbonate.

[0014] In one embodiment, in step S20, the temperature of the second heat treatment is 700° C. to 900° C., and the time of the second heat treatment is 10 h to 14 h.

[0015] In one embodiment, in step S30, the acid is selected from at least one of sulfuric acid, nitric acid, hydrochloric acid, oxalic acid and carbonic acid; and / or

[0016] The temperature of the third heat treatment is 200° C. to 600° C., and the time of the third heat treatment is 2 h to 6 h.

[0017] Furthermore, the present invention also provides the use of the above-mentioned modified lithium-rich manganese-based material in the preparation of battery electrodes.

[0018] The modified lithium-rich manganese-based material provided by the present invention has a spinel coating layer on its surface and a specific proportion of oxygen vacancies, which fully utilizes the spinel coating layer to provide a three-dimensional lithium ion channel, and can accelerate the Li + The diffusion of the modified material can improve the rate performance of the material and the transmission efficiency of lithium ions. At the same time, it can reduce the erosion of the electrolyte on the main structure of the material. Further, it can cooperate with the formed oxygen vacancies to inhibit the irreversible oxygen precipitation, reduce structural rearrangement, maintain the stability of the material structure, and make the lithium battery have better rate performance and better cycle stability after the modified material is used as an electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The modified lithium-rich manganese-based material Li prepared in Example 1 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and unmodified Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 X-ray diffraction (XRD) pattern of O2;

[0020] Figure 2 The modified lithium-rich manganese-based material Li prepared in Example 1 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and unmodified Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 Raman spectrum of O2;

[0021] Figure 3 The modified lithium-rich manganese-based material Li prepared in Example 1 1.2 Ni 0.13 Co 0.13 Mn 0.54 Transmission electron microscopy (TEM) image of O2;

[0022] Figure 4 The modified lithium-rich manganese-based material Li prepared in Example 1 1.2 Ni 0.13 Co 0.13 Mn 0.54 Electron paramagnetic resonance (EPR) pattern of O2;

[0023] Figure 5 The modified lithium-rich manganese-based material Li prepared in Example 1 and Comparative Example 1 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and unmodified Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 First coulombic efficiency diagram of the O2 assembled battery at 0.1C;

[0024] Figure 6 The modified lithium-rich manganese-based material Li prepared in Examples 1, 2, and 3 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and unmodified Li1.2 Ni 0.13 Co 0.13 Mn 0.54 Rate performance diagram of O2 assembled battery;

[0025] Figure 7 The modified lithium-rich manganese-based material Li prepared in Examples 1, 2, and 3 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and unmodified Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 Electrochemical cycling performance of O2 assembled battery at 0.3C. DETAILED DESCRIPTION

[0026] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0027] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the invention, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present invention, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0028] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0029] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the technical field to which this invention belongs. The terms used in the description of the present invention herein are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0031] The present invention provides a modified lithium-rich manganese-based material, including a spinel phase layer of a lithium-rich manganese-based material containing a first oxygen vacancy and a layered phase layer of a lithium-rich manganese-based material containing a second oxygen vacancy, wherein the spinel phase layer coats the layered phase layer, and the chemical formula of the lithium-rich manganese-based material is 0 < x < 1, the spinel phase of the lithium-rich manganese-based material accounts for 1% to 10% of the mass percentage of the modified lithium-rich manganese-based material, the first oxygen vacancy accounts for 1 at% to 5 at% of the oxygen atoms of the modified lithium-rich manganese-based material, and the second oxygen vacancy accounts for 1 at% to 3 at% of the oxygen atoms of the modified lithium-rich manganese-based material.

[0032] Preferably, x is 0.8.

[0033] In a specific example, the spinel phase of the lithium-rich manganese-based material accounts for 3% to 9% of the mass percentage of the modified lithium-rich manganese-based material, and the first oxygen vacancy accounts for 1 at% to 4 at% of the oxygen atoms of the modified lithium-rich manganese-based material.

[0034] In a specific example, the thickness of the spinel phase layer of the lithium-rich manganese-based material is 5 nm to 15 nm.

[0035] The cooperation of the spinel phase coated on the outer surface of the modified lithium-rich manganese-based material provided by the present invention with a specific proportion of oxygen vacancies makes full use of the three-dimensional lithium ion channels provided by the spinel coating layer, which can accelerate the diffusion of Li + , improve the rate performance of the material, improve the transmission efficiency of lithium ions, and at the same time can reduce the erosion of the electrolyte on the main structure of the material. Further, in cooperation with the formed oxygen vacancies, it can inhibit the precipitation of irreversible oxygen, reduce the structural rearrangement, maintain the structural stability of the material, and make the modified material have better rate performance and better cycle stability when used as an electrode in a lithium battery.

[0036] The present invention further provides a preparation method of a modified lithium-rich manganese-based material, including the following steps S10 to step S30.

[0037] Step S10: Prepare metal salts according to the ratio of metal nickel, metal cobalt and metal manganese in the above-mentioned lithium-rich manganese-based material, mix the first metal salt and the precipitant in a mass ratio of (1 to 3):(2 to 5), and perform the first heat treatment to prepare a precursor.

[0038] In a specific example, in step S10, the precipitant is selected from at least one of ammonium bicarbonate, urea and sodium carbonate.

[0039] It can be understood that the first metal salt and the precipitant are dissolved in solvents to prepare a metal salt solution and a precipitant solution respectively, and then mixed. Specifically, the solvent can be but is not limited to at least one selected from ethylene glycol, water and polyethylene glycol.

[0040] Furthermore, the first metal salt solution is a first metal salt solution prepared by dissolving a metal salt in ethylene glycol and having a concentration of 1 mol / L to 3 mol / L.

[0041] Furthermore, the precipitant solution is prepared by mixing the precipitant and the solvent in a ratio of (2-5) g: (15-35) mL.

[0042] In a specific example, in step S10, the anion in the first metal salt is selected from at least one of acetate, sulfate and nitrate, and preferably the anion in the first metal salt is acetate.

[0043] In order to mix the first metal salt solution and the precipitant solution uniformly, stirring is performed at room temperature for 1 h to 2 h, and then the first heat treatment is performed.

[0044] In a specific example, in step S10, the temperature of the first heat treatment is 150° C. to 600° C., and the time of the first heat treatment is 10 h to 25 h.

[0045] It can be understood that the first heat treatment is a staged heat treatment, the temperature of the first stage heat treatment in the first heat treatment is 150°C to 200°C, and the time of the first stage heat treatment in the first heat treatment is 8h to 15h.

[0046] Specifically, the temperature of the first stage heat treatment may be, but is not limited to, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C.

[0047] Furthermore, the time of the first stage heat treatment may be, but is not limited to, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h.

[0048] It can be understood that the temperature of the second stage heat treatment in the first heat treatment is 300° C. to 600° C., and the time of the second stage heat treatment in the first heat treatment is 2 h to 10 h.

[0049] Specifically, the time for the second stage heat treatment may be, but is not limited to, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C or 600°C.

[0050] Furthermore, the time of the second stage heat treatment may be, but is not limited to, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.

[0051] Step S20: Mix the precursor and the lithium salt in a molar ratio of the first metal in the precursor to lithium of 1:(1-2), perform a second heat treatment, and prepare a pre-modified lithium-rich manganese-based material.

[0052] It is understood that the lithium salt may be, but is not limited to, lithium hydroxide.

[0053] In a specific example, in step S20, the temperature of the second heat treatment is 700° C. to 900° C., and the time of the second heat treatment is 10 h to 14 h.

[0054] Specifically, the temperature of the second heat treatment may be, but is not limited to, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 880°C or 900°C.

[0055] Furthermore, the time of the second heat treatment may be, but is not limited to, 10 h, 11 h, 12 h, 13 h or 14 h.

[0056] It can be understood that the temperature is increased to the second heat treatment temperature at a heating rate of 1° C. / min to 5° C. / min.

[0057] Specifically, the heating rate may be, but is not limited to, 1° C. / min, 2° C. / min, 3° C. / min, 4° C. / min or 5° C. / min.

[0058] Step S30: the pre-modified lithium-rich manganese-based material is dispersed in an acid aqueous solution with a pH value of 5-7.

[0059] In a specific example, in step S30, the acid is selected from at least one of sulfuric acid, nitric acid, hydrochloric acid, oxalic acid and carbonic acid.

[0060] Preferably, the pH value is 0.01 mol / L to 0.08 mol / L of an aqueous solution of oxalic acid.

[0061] It can be understood that, in order to achieve effective modification of the material, generally 0.5 g to 5 g of the pre-modified lithium-rich manganese-based material is taken and fully stirred in the aqueous solution of the above acid.

[0062] Furthermore, the stirring time may be 0.1 h to 5 h.

[0063] It can be understood that the stirring time can be, but is not limited to, 0.1 h, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h.

[0064] In a specific example, the temperature of the third heat treatment is 200° C. to 600° C., and the time of the third heat treatment is 2 h to 6 h.

[0065] Specifically, the temperature of the third heat treatment may be, but is not limited to, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C.

[0066] Furthermore, the time of the third heat treatment may be, but is not limited to, 2 h, 3 h, 4 h, 5 h or 6 h.

[0067] Furthermore, the present invention also provides the use of the above-mentioned modified lithium-rich manganese-based material in the preparation of battery electrodes.

[0068] It is understandable that the above-mentioned battery can be, but does not include, a lithium battery.

[0069] In the preparation process of the modified lithium-rich manganese-based material, the formation of spinel phase and oxygen vacancies can be quantitatively induced by controlling the acid concentration and replacement time, and different contents of spinel phase and oxygen vacancies can be successfully produced on the surface of the lithium-rich manganese-based material. The spinel coating layer is fully utilized to provide a three-dimensional lithium ion channel, which can accelerate the Li + The diffusion of the modified material can improve the rate performance of the material and the transmission efficiency of lithium ions. At the same time, it can reduce the erosion of the electrolyte on the main structure of the material. Further, it can cooperate with the formed oxygen vacancies to inhibit the irreversible oxygen precipitation, reduce structural rearrangement, maintain the stability of the material structure, and make the lithium battery have better rate performance and better cycle stability after the modified material is used as an electrode.

[0070] The following specific examples are provided to further illustrate the modified lithium-rich manganese-based material and the preparation method thereof. In the following specific examples, unless otherwise specified, all raw materials can be sourced from commercial sources.

[0071] Example 1

[0072] The modified lithium-rich manganese-based material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54The preparation method of O2 is as follows: according to the molar ratio of Mn:Ni:Co being 4:1:1, 1.635g of manganese acetate tetrahydrate, 0.416g of cobalt acetate tetrahydrate and 0.416g of nickel acetate tetrahydrate are taken and dissolved in 40mL of ethylene glycol solution to obtain a first metal salt solution with a molar concentration of 2mol / L, which is recorded as solution a; 3.5g of ammonium bicarbonate is dissolved in a mixed solution of 25mL of water and polyethylene glycol 400 (volume ratio of 1:1) to obtain solution b; under magnetic stirring, the ammonium bicarbonate solution b is pumped into the above-mentioned first metal salt solution a through a peristaltic pump, and then put into a high-pressure reactor, the outer shell is tightened, and the temperature is kept at 180°C for 10h; and the mixture is cooled. The mixture was centrifuged and then cooled to obtain a precipitate; the precipitate was placed in a muffle furnace and kept warm at 500°C for 5 hours to obtain a precursor; the first metal in the precursor and lithium hydroxide were mixed and ground in a molar ratio of 1:1.06, and then uniformly sent into a muffle furnace, heated to 800°C at a heating rate of 3°C / min and calcined for 12 hours, and then taken out after cooling to room temperature to obtain a pre-modified lithium-rich manganese-based material; 0.5g of the pre-modified lithium-rich manganese-based material was taken, dissolved in 0.02mol / L oxalic acid solution (0.108g oxalic acid, 60mL deionized water), stirred for 30min, then filtered and dried, and placed in a muffle furnace for heat treatment at 500°C for 5h.

[0073] The unmodified lithium-rich manganese-based material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, and the modified lithium-rich manganese-based material Li rich in spinel phase and oxygen vacancies 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 was used for crystal structure analysis and electrochemical performance test, and the prepared half-cell was subjected to constant current charge and discharge test. The half-cell was assembled in an argon glove box (water and oxygen content was less than 0.01 ppm), the positive electrode was the modified lithium-rich manganese-based material in Example 1, the counter electrode was a lithium sheet, the diaphragm was Celgard 2500, the electrolyte was a mixture of dimethyl carbonate, diethyl carbonate and ethyl carbonate in a volume ratio of 1:1:1, and the solute concentration was 1 mol / L LiPF6; the half-cell model was 2025.

[0074] The test results are as follows: Figure 1 It can be seen from the XRD that the unmodified Li 1.2 Ni 0.13 Co 0.13 Mn 0.54The diffraction peaks and spectra of the samples of O2 and Example 1 are basically consistent. Except for some characteristic peaks belonging to the Li2MnO3 type between 20°-25°, the other diffraction peaks belong to the hexagonal α-NaFeO2 structure. Both the (006) / (012) and (018) / (110) peaks have obvious separation phenomena, indicating that the material has a good layered structure. Through XRD refinement, the modified material was obtained, and the mass percentage of the spinel phase in the modified material was 7.5%. The oxygen vacancies in the modified material accounted for 4.7at% of the oxygen atoms, while the oxygen vacancies in the original material accounted for 2.2at% of the oxygen atoms, proving that the spinel phase and oxygen vacancies were successfully introduced after modification.

[0075] Figure 2 For unmodified Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 and Li of Example 1 1.2 Ni 0.13 Co 0.13 Mn 0.54 Raman spectrum of O2, 480 cm -1 The peak at 480cm is the characteristic peak of C2 / m; -1 and 600cm -1 The characteristic peaks near the g and elongation mode A 1g , which is the vibration mode of MO in R-3m; compared with the unmodified material, the material of Example 1 has a -1 The peak near is attributed to the stretching vibration of the Mn-O bond in the spinel phase, indicating the presence of the spinel phase in Example 1.

[0076] Figure 3 is Li of Example 1 1.2 Ni 0.13 Co 0.13 Mn 0.54 From the transmission electron microscope image of O2, it can be seen that the material of Example 1 has two lattice fringes with different spacings, among which the lattice fringes with a crystal plane spacing of 0.47nm correspond to the (003) crystal plane in the layered phase, and the lattice spacing of 0.21nm corresponds to the (400) crystal plane of the spinel phase, indicating that the spinel phase is successfully introduced into the material of Example 1.

[0077] Figure 4 For unmodified Li 1.2 Ni 0.13 Co 0.13 Mn 0.54The electron paramagnetic resonance EPR spectrum of O2 and Example 1 shows that the oxygen vacancy defect peak of Example 1 material is enhanced, indicating that a certain number of oxygen vacancies are formed in the sample treated by this method, which matches the XRD refinement data.

[0078] Figure 5 The first coulombic efficiency comparison chart of the two materials shows that the first coulombic efficiency of the material in Example 1 can reach 94% at 0.1C, while the first coulombic efficiency of the original material is only 84%. In Comparative Example 1, due to the excessive content of the spinel phase, a long discharge platform appears at 2.8V, and the coulombic efficiency increases to 148%, but the discharge specific capacity is greatly reduced compared with the original material and Example 1, mainly due to the excessive spinel phase and oxygen vacancies in Comparative Example 1. The improvement in the first coulombic efficiency of the modified material is mainly attributed to the reduction in irreversible oxygen loss after charging at 4.5V. When there are too many oxygen vacancies and spinel phases in the lithium-rich material, it will lead to unfavorable factors such as a decrease in the specific capacity of the material and structural instability.

[0079] Figure 6 The rate performance comparison diagram of the two materials shows that the material rich in spinel phase and oxygen vacancies in Example 1 shows a higher discharge specific capacity, especially at the rates of 2C and 4C, which can release 191 mAh·g -1 and 158mAh g -1 Specific capacity.

[0080] Figure 7 It can be seen that after 200 cycles at 0.3C, the discharge capacity of Example 1 can still reach 220 mAh g -1 The capacity retention rate is 88%, the capacity retention rate of Example 2 is 77%, and the capacity retention rate of Example 2 is 74%. 1.2 Ni 0.13 Co 0.13 Mn 0.54 The capacity retention rate of O2 material is only 63%, indicating that the presence of spinel phase and oxygen vacancies can effectively improve the cycle stability of the material.

[0081] The above test results prove that the existence of spinel phase can accelerate the diffusion rate of lithium ions, improve the rate performance of the material, and reduce the corrosion of the electrolyte on the material body; oxygen vacancies can inhibit the irreversible oxygen loss during the first charge and discharge process of the material, improve the first coulombic efficiency of the material, and improve the structural stability of the material. Therefore, constructing spinel phase and oxygen vacancies in lithium-rich materials can effectively improve the cycle stability and rate performance of the material.

[0082] Example 2

[0083] The modified lithium-rich manganese-based material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The preparation method of O2 is as follows: 1.635g of manganese acetate tetrahydrate, 0.416g of cobalt acetate tetrahydrate, and 0.416g of nickel acetate tetrahydrate are dissolved in 40mL of ethylene glycol solution to obtain a first metal salt solution with a molar concentration of 2mol / L, which is recorded as solution a; 3.5g of ammonium bicarbonate is dissolved in a mixed solution of 25mL of water and polyethylene glycol 400 to obtain solution b; under magnetic stirring, the ammonium bicarbonate solution b is pumped into the above-mentioned first metal salt solution a through a peristaltic pump, and then placed in a high-pressure reactor, the outer shell is tightened, and the temperature is kept at 180°C for 10h; after cooling, centrifugation is performed to obtain a precipitate; the precipitate is The material is placed in a muffle furnace and kept warm at 500°C for 5h to obtain a precursor; the first metal in the precursor and lithium hydroxide are mixed and ground according to a molar ratio of 1:1.06, and then uniformly sent into a muffle furnace, heated to 800°C at a heating rate of 3°C / min and calcined for 12h, and then taken out after cooling to room temperature to obtain a pre-modified lithium-rich manganese-based material; 0.5g of the pre-modified lithium-rich manganese-based material is taken, dissolved in 0.01mol / L oxalic acid solution (0.054g oxalic acid, 60mL deionized water), stirred for 30min, then filtered and dried, and placed in a muffle furnace for heat treatment at 500°C for 5h.

[0084] The mass percentage of the spinel phase of the modified lithium-rich manganese-based material provided in this embodiment is 4.9%.

[0085] Example 3

[0086] The modified lithium-rich manganese-based material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54The preparation method of O2 is as follows: 1.635g of manganese acetate tetrahydrate, 0.416g of cobalt acetate tetrahydrate, and 0.416g of nickel acetate tetrahydrate are dissolved in 40mL of ethylene glycol solution to obtain a first metal salt solution with a molar concentration of 2mol / L, which is recorded as solution a; 3.5g of ammonium bicarbonate is dissolved in a mixed solution of 25mL of water and polyethylene glycol 400 to obtain solution b; under magnetic stirring, the ammonium bicarbonate solution b is pumped into the above-mentioned first metal salt solution a through a peristaltic pump, and then placed in a high-pressure reactor, the outer shell is tightened, and the temperature is kept at 180°C for 10h; after cooling, centrifugation is performed to obtain a precipitate; the precipitate is separated and the mixture is stirred for 2 hours. The precipitate is placed in a muffle furnace and kept at 500°C for 5 hours to obtain a precursor; the first metal in the precursor and lithium hydroxide are mixed and ground according to a molar ratio of 1:1.06, and then sent into a muffle furnace for uniform mixing, and the temperature is increased to 800°C at a heating rate of 3°C / min, and calcined for 12 hours, and then taken out after cooling to room temperature to obtain a pre-modified lithium-rich manganese-based material; 0.5g of the pre-modified lithium-rich manganese-based material is taken, dissolved in 0.01mol / L oxalic acid solution (0.054g oxalic acid, 60mL deionized water), stirred for 60min, then filtered and dried, and placed in a muffle furnace for heat treatment at 500°C for 5h.

[0087] The mass percentage of the spinel phase of the modified lithium-rich manganese-based material provided in this embodiment is 12%.

[0088] Comparative Example 1

[0089] The modified lithium-rich manganese-based material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The preparation method of O2 is as follows: 1.635g of manganese acetate tetrahydrate, 0.416g of cobalt acetate tetrahydrate, and 0.416g of nickel acetate tetrahydrate are dissolved in 40mL of ethylene glycol solution to obtain a first metal salt solution with a molar concentration of 2mol / L, which is recorded as solution a; 3.5g of ammonium bicarbonate is dissolved in a mixed solution of 25mL of water and polyethylene glycol 400 to obtain solution b; under magnetic stirring, the ammonium bicarbonate solution b is pumped into the above-mentioned first metal salt solution a through a peristaltic pump, and then placed in a high-pressure reactor, the outer shell is tightened, and the temperature is kept at 180°C for 10h; after cooling, centrifugation is performed to obtain a precipitate; The precipitate is placed in a muffle furnace and kept at 500°C for 5 hours to obtain a precursor; the first metal in the precursor and lithium hydroxide are mixed and ground according to a molar ratio of 1:1.06, and then sent into a muffle furnace, heated to 800°C at a heating rate of 3°C / min, calcined for 12 hours, and taken out after cooling to room temperature to obtain a pre-modified lithium-rich manganese-based material; 0.5g of the pre-modified lithium-rich manganese-based material is taken, dissolved in 0.1mol / L oxalic acid solution (0.54g oxalic acid, 60mL deionized water), stirred for 30min, then filtered and dried, and placed in a muffle furnace for heat treatment at 500°C for 5h.

[0090] Compared with the unmodified material, the modified lithium-rich manganese-based material rich in spinel phase and oxygen vacancies provided by the present invention has a capacity retention rate of 88% after 200 cycles at 0.3C in the electrochemical window of 2V to 4.65V after being assembled and charged, and the discharge specific capacity is maintained at 220mAh·g -1 At 4C high current, the discharge capacity is as high as 158mAh g -1 , with good rate performance and cycle stability.

[0091] The technical features of the above embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0092] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present invention, several modifications and improvements can be made, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description can be used to interpret the contents of the claims.

Claims

1. A modified lithium-rich manganese-based material, characterized in that: It includes a spinel phase layer containing a lithium-rich manganese-based material with a first oxygen vacancy and a layered phase layer containing a lithium-rich manganese-based material with a second oxygen vacancy. Among them, the spinel phase layer coats the layered phase layer, and the chemical formula of the lithium-rich manganese-based material is Li 2-x Ni x / 6 Co x / 6 Mn 2x / 3 O2, where 0 < x < 1. The spinel phase of the lithium-rich manganese-based material accounts for 1% to 10% of the mass percentage in the modified lithium-rich manganese-based material. The first oxygen vacancy accounts for 1 at% to 5 at% of the oxygen atoms in the modified lithium-rich manganese-based material, and the second oxygen vacancy accounts for 1 at% to 3 at% of the oxygen atoms in the modified lithium-rich manganese-based material.

2. The modified lithium-rich manganese-based material according to claim 1, characterized in that: The spinel phase of the lithium-rich manganese-based material accounts for 3% to 9% by mass of the modified lithium-rich manganese-based material, and the first oxygen vacancies account for 1 at% to 4 at% of the oxygen atoms in the modified lithium-rich manganese-based material.

3. The modified lithium-rich manganese-based material according to claim 1, characterized in that: The thickness of the spinel phase layer of the lithium-rich manganese-based material is 5 nm to 15 nm.

4. A method for preparing the modified lithium-rich manganese-based material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S10: preparing a first metal salt according to the ratio of metal nickel, metal cobalt and metal manganese in the lithium-rich manganese-based material, mixing the first metal salt with a precipitant in a mass ratio of (1-3): (2-5), performing a first heat treatment, and preparing a precursor; S20: mixing the precursor and the lithium salt in a molar ratio of the first metal in the precursor to lithium of 1: (1-2), and performing a second heat treatment to prepare a pre-modified lithium-rich manganese-based material; S30: dispersing the pre-modified lithium-rich manganese-based material in an aqueous solution of 0.01 mol / L to 0.08 mol / L oxalic acid and stirring the solution for 0.1 h to 5 h, filtering the solution and performing a third heat treatment.

5. The method for preparing the modified lithium-rich manganese-based material according to claim 4, characterized in that: In step S10, the anion in the metal salt is selected from at least one of acetate, sulfate and nitrate.

6. The method for preparing the modified lithium-rich manganese-based material according to claim 4, characterized in that: In step S10, the temperature of the first heat treatment is 150°C to 600°C, and the time of the first heat treatment is 10 h to 25 h.

7. The method for preparing the modified lithium-rich manganese-based material according to claim 4, characterized in that: In step S10, the precipitant is selected from at least one of ammonium bicarbonate, urea and sodium carbonate.

8. The method for preparing the modified lithium-rich manganese-based material according to claim 4, characterized in that: In step S20, the temperature of the second heat treatment is 700°C to 900°C, and the time of the second heat treatment is 10 h to 14 h.

9. The method for preparing the modified lithium-rich manganese-based material according to any one of claims 4 to 8, characterized in that: In step S30, the temperature of the third heat treatment is 200°C to 600°C, and the time of the third heat treatment is 2 h to 6 h.

10. Use of the modified lithium-rich manganese-based material according to any one of claims 1 to 3 in the preparation of battery electrodes.

Citation Information

Patent Citations

  • Lithium ion battery anode material adopting in-situ developed heterogeneous core-shell structure and preparation method of material

    CN105514362A

  • Modified lithium-rich manganese-based oxide positive electrode material and preparation method and application thereof

    CN111883746A